2015
DOI: 10.18632/aging.100729
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomic analysis reveals overlapping and distinct features of chronologically long-lived yeast populations

Abstract: Yeast chronological lifespan (CLS) is extended by multiple genetic and environmental manipulations, including caloric restriction (CR). Understanding the common changes in molecular pathways induced by such manipulations could potentially reveal conserved longevity mechanisms. We therefore performed gene expression profiling on several long-lived yeast populations, including an ade4∆ mutant defective in de novo purine (AMP) biosynthesis, and a calorie restricted WT strain. CLS was also extended by isonicotinam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 57 publications
(88 reference statements)
4
19
0
Order By: Relevance
“…However, the CLS-extending compound isonicotinamide (INAM) clearly extended CLS of the snf1Δ mutant ( Fig. 1E and G), consistent with INAM changing the stationary-phase gene expression profile differently from CR (24) and indicating that INAM extends CLS through a more Snf1-independent mechanism.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…However, the CLS-extending compound isonicotinamide (INAM) clearly extended CLS of the snf1Δ mutant ( Fig. 1E and G), consistent with INAM changing the stationary-phase gene expression profile differently from CR (24) and indicating that INAM extends CLS through a more Snf1-independent mechanism.…”
Section: Resultssupporting
confidence: 60%
“…Expression profiling of cells grown to stationary phase under CR conditions revealed that the genes involved in acetate utilization were upregulated compared to those in nonrestricted (NR) yeast cells (24). Since Snf1 was known to be important for alternative carbon source utilization (25), we hypothesized that it was mediating the CLS extension induced by CR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiration increases with reduction of glucose concentration to 0.5% or lower (“calorie-restricted”) from 2% (“non-restricted”) (Ocampo and others 2012; Pan and others 2011), but the significance of this metabolic change with regard to the many genetic effects on the CLS phenotype is not well understood, for example, there is less organic acid production by cells growing in media with lower glucose (Burtner and others 2009a). Thus, aerobic glycolysis and fermentation of glucose in the log phase of growth, organic acid production and secretion into the media, and its consequent effects on CLS represent an important mechanism of CLS, which can be greatly affected by media conditions and aeration status (Burtner and others 2009a; Murakami and others 2011; Ocampo and others 2012; Wierman and others 2015). Buffering the media (e.g., in the Longo lab media), or washing away the acetic acid in conditioned media, and aging in water can also potentially increase CLS.…”
Section: Resultsmentioning
confidence: 99%
“…The “acetic acid mechanism” appears to be fairly complex, but it may further be only one of many related or independent mechanisms of CLS. The number of factors that influence CLS is only beginning to be characterized (Matecic and others 2010; Ocampo and others 2012; Wierman and others 2015). …”
Section: Resultsmentioning
confidence: 99%